Financial literacy, financial self-efficacy and financial account ownership behavior in Pakistan - Nimra Noor; Irem Batool; Hafiz Muhammad Arshad (Cogent Economics & Finance, 2020)
Study examines the role of financial literacy and financial self-efficacy of individuals in explaining their behavior to have financial accounts. Study has used the questionnaire based survey and collected the data responses from 564 adults belonging to Sahiwal division. The binary logistic regression model is utilized to estimate the probability of having financial accounts in relation to individual's financial literacy and financial self-efficacy level. Estimated results show that individual's financially literacy level is positively related with individual's account ownership model among the selected group. While individual's financial self-efficacy level does not explain any positive significant impact on individual's account ownership model. Other socio-demographic variables like gender, marital status, education, occupation, and income level are also found to have influential impact on the individuals' account ownership behavior in Pakistan. Study recommends that financial literacy is pertinent to have equitable financial inclusion in the economy.
Keywords: G20; G40; G41; 330; financial inclusion; financial literacy; financial self-efficacy; Pakistan